2019
DOI: 10.1097/meg.0000000000001290
|View full text |Cite
|
Sign up to set email alerts
|

What recovery position should patients adopt after percutaneous liver biopsy?

Abstract: Introduction Percutaneous liver biopsy (PLB) is an invasive procedure used for the assessment of liver diseases. The patient’s recovery position after the PLB differs among hospitals and departments. This study aims to evaluate adverse events and patient acceptability according to the recovery position adopted after the PLB. Patients and methods From September 2014 to March 2017, patients submitted to PLB were randomly assigned to a recovery position ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…In our study, the incidence of low blood pressure following the PLB was low (1.5%), similar to previous reports 7,20 . It may occur due to bleeding, vasovagal reflex associated with pain, or even as a side effect of sedative drugs, such as midazolam 4,7,8 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the incidence of low blood pressure following the PLB was low (1.5%), similar to previous reports 7,20 . It may occur due to bleeding, vasovagal reflex associated with pain, or even as a side effect of sedative drugs, such as midazolam 4,7,8 .…”
Section: Discussionsupporting
confidence: 92%
“…According to the literature, the patient's position after the PLB does not affect the rate and severity of complications 20 , so our patients decided a comfortable position to rest. At our center, the protocol is to maintain observation for up to 4 to 6 hours after PLB, but the most appropriate period has not been well defined in the literature and it can last from 2 to 8 hours 4,9,[21][22][23] .…”
Section: Discussionmentioning
confidence: 91%
“…In a previous study, Chris et al reported no other severe complications except pain (11). In contrast, Rita et al reported the incidence of vasovagal reaction in two cases (2.2%) (10), which was in line with the previous study (17,25). As the two RCTs enrolled in this study involved inadequate cases, we did not observe any complications (e.g., hemorrhage).…”
Section: Discussionsupporting
confidence: 72%
“…In this study, we enrolled two RCTs, and then the metaanalysis was conducted, which showed that the post-PLB pain score in the supine position was significantly lower than that of the combined position at T0. This may be related to the local stimulation-induced pain sensation by RRP or during the body position changes (10,11). There were no statistical differences in the post-PLB pain score among the patients in the supine position, RRP, and CRP at T2 and T4, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…Most studies were retrospective (20/30, all except [21][22][23][24][25][26][27][28][29]). Most were single-center accounts, with 3 being multi-center studies that nevertheless represented the majority of samples (56,058 of 64,356 biopsies; Table 1).…”
Section: Study and Cohort Characteristicsmentioning
confidence: 99%